Principales familias de insectos enemigos naturales de Sibine fusca Stoll 1781, (Lepidoptera – Limacodidae) en el cultivo de banano (Musa paradisiaca) - Veloz Pérez, Renato Heriberto (2022)
Banana (Musa paradisiaca) is the main agricultural export product in Ecuador, generating a great socio-economic impact in the country. However, this crop is constantly attacked by pests and diseases throughout its production cycles, which is why the use of natural enemies as biological controllers is emphasized. S. fusca is an insect that belongs to the Lepidoptera order of the Limacodidae family, its larvae feed in a gregarious way, initially the damage is caused on de margins of the leaves, they leave perforations on the edges, destroying a large part of the leaf area, causing the decrease of the productive system. From the first instar they feed in the place where their eggs are laid, they remain grouped and consume up to half the thickness of the leaf blade, then they consume the entire leaf, leaving only the vein. Through the technique of using natural enemies, it is possible to keep the damage levels of S. fusca below the economic threshold. Preventing economic losses since a larva can devour 40 cm of leaf, which means 45 or 50 larvae can completely devour a leaf. Among the natural enemies of this pest are mainly the parasitoids of the Braconidae, Ichneumonidae, Tachinidae, Chalcididae, Eulophidae families and predators of the Pentatomidae family, among others, being the parasitoids the biological controllers that exert greater control over this pest.